KARAKTERISTIK MI TINGGI ANTIOKSIDAN DARI DAUN KELOR (Moringa oleifera L.) DAN DAUN BELUNTAS (Pluchea indica L.) - Wulantika, W.; Supriyanto, Supriyanto; Fakhry, M. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Moringa (Moringa Oleifera) and beluntas (Pluchea Indica) plants contain high antioxidants so they can be used as functional foods. The purpose of this study was to find out the characteristics of noodles made from moringa leaf extract and beluntas. The study used a complete non-factorial random design with 5 variations of the noodle-making formula. Observed paramaters include color analysis, antioxidants and sensory tests. The research data was analyzed using the F test at the 5% signification level if there was a noticeable difference followed by the DMRT?5% test with the help of SPSS software version 21.  The results showed that the use of Moringa leaves in the form of porridge can increase its antioxidant content by a value of 11.63.%.